Estrategia para la producción sostenible de muebles en el “Comercial Fannycita” de la ciudad de Ambato - Chicaiza Chicaiza, Alex Bladimir (2025)
The article addresses strategies for sustainable furniture production at "Comercial Fannycita," a company based in Ambato, Ecuador. The research identifies key issues such as the use of uncertified wood, solid waste generation, and low energy efficiency. Using a mixed and descriptive approach, solutions are proposed, including the use of FSC-certified wood, recycled materials, and energy-efficient technologies. Additionally, the implementation of recycling programs and the adoption of renewable energy sources are suggested. These strategies aim to reduce environmental impact, decrease operational costs, and improve business competitiveness. The study highlights the importance of incorporating sustainability as a strategic pillar, ensuring regulatory compliance, and aligning with the growing demand from conscious consumers. The results emphasize the feasibility of sustainable practices to transform the furniture industry in both local and global contexts.